2009
DOI: 10.5194/hess-13-1249-2009
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of canopy component temperatures through Bayesian inversion of directional thermal measurements

Abstract: Abstract. Evapotranspiration is usually estimated in remote sensing from single temperature value representing both soil and vegetation. This surface temperature is an aggregate over multiple canopy components. The temperature of the individual components can differ significantly, introducing errors in the evapotranspiration estimations. The temperature aggregate has a high level of directionality. An inversion method is presented in this paper to retrieve four canopy component temperatures from directional br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Chehbouni et al [2001a] found that accurate dual angles of measured directional radiative temperatures could be used to estimate sensible heat flux of sparse vegetation canopies. Timmermans et al [2009] applied an inversion method to retrieve four canopy component temperatures from directional brightness temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Chehbouni et al [2001a] found that accurate dual angles of measured directional radiative temperatures could be used to estimate sensible heat flux of sparse vegetation canopies. Timmermans et al [2009] applied an inversion method to retrieve four canopy component temperatures from directional brightness temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Many optimized algorithms, such as least-square, Bayes, and genetic algorithms have been proposed to improve the inversion results [16,[29][30][31]. Since only two observed angles are used and direct results can be clear, we do not use an optimization algorithm in this paper.…”
Section: Inversion Methodsmentioning
confidence: 99%
“…Using these RTMs, the temperatures of surface sunlit and shaded areas and their vertical distributions can be inverted. For instance, Timmermans et al [16] retrieved four-component (sunlit and shaded leaves and sunlit and shaded soil) temperatures using the four-stream scattering by arbitrarily inclined leaves (4SAIL) model. Colaizzi et al [22] proposed a radiometer footprint model to estimate sunlit and shaded components for row crops.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations